Designing Computer Assisted Language Learning Media For Junior High School Student At SMP N 1 Wonosobo - Setiawan., Arfin; , Aryati Prasetyarini, M.Pd; , Drs. Sigit Haryanto, M.Hum (2013)
This research aims at describing the process of designing an interactive learning medium known as Computer Assisted Language Learning at SMP N 1 Wonosobo. It is conducted to describe stages of developing a learning medium, problem faced while developing a medium, and problem solving by the researcher. In this research the data are derived from event, informant, and document. There are three techniques in collecting the data namely: observation, interview, and document analysis. The data achieved from informations related to media use in the classroom teaching learning process, in form of the field note, script interview and document. Designing Computer Assisted Language Learning Media for Junior High School Student at SMP N I Wonosobo, the results are 1) In the developing of Computer Assisted Language Learning Media the writer used four stage according to the Thiagarajan theory. They are Define, Design, Develop and Disseminate. 2) The problem faced by the researcher in Designing Computer Assisted language Learning Media founded in Develop stage are, feedback answer, Material Composing, and Actionscript Programming. 3) To solve those problems, researcher doing some revision to the product in the Develop stage by giving direct feedback for the answer one by one, correcting material used in the medium and giving suggestion to the other media designer to contact an expert programmer while writing the Actionscript through the media.